Brand image, product quality, and price as antecedent of purchase decision - Susanti, Dewi (Universitas Ahmad Dahlan, 2025)
Purpose-Currently, there are various brands of various product variants on the market. This is one of the effects of increasing business competition. As a result of this phenomenon, consumers need to consider carefully before purchasing. This study analyzes the influence of brand image, product quality, and price on consumer purchasing decisions. Methodology-The object of this study is Indonesian students who have purchased sneakers in their daily lives. The sample consisted of 108 respondents obtained using purposive sampling. The data analysis methods used were validity and reliability tests and hypothesis testing using SPSS 22 analysis tools. Findings-The results indicate that, partially, brand image, product quality, and price positively affect purchasing decisions. A positive brand image, consistent product quality, and prices that align with product quality influence consumers' decisions to buy sneakers. Research Limitations-The limitation of this study is the relatively small number of respondents, even though it covers students throughout Indonesia, so the results of this study cannot be said to represent the majority of sneaker users in various regions of Indonesia. Further research could increase the number of respondents, focus on a specific area in Indonesia, or focus on a particular sneaker brand. Novelty-This study can be used as a reference for future researchers and as a guideline for sneaker manufacturers to encourage consumer purchasing decisions by considering the factors analyzed in this study. This study analyzes sneaker users in general, not specific to certain brands.